The Application of Communicative Language Teaching Method in English Language Learning - Widyaningrum, Winda; Wulandari, Wita (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
English learning in Indonesia is a compulsory from elementary grade school, and this is not easy for the teacher and the learner because the mother tongue of Indonesia is Bahasa and we do not have the concept of second language. The problems that happening often are the lack of interest and the motivation of the learners when they learn English, mostly happens because the method used by the teacher is deemed as boring and unsuitable for them. This study uses qualitative method to understand the function, benefit, and the usage of Communicative Language Teaching and to solve the problems on learning English in Indonesia.